Islamic Education Learning for Mentally Disabled in Muhammadiyah Extraordinary School, Dekso, Kulonprogo - Difaul Husna (Educan : Jurnal Pendidikan Islam, 2020)
Humans have three dimensions that are central to human personality, body, mind (science) and spirit (faith). As a religion of nature, Islam cannot accept bodily strength without the power of reason and faith, and vice versa. But the fact is we find many children with special needs around us. Children with special needs need a spiritual touch, to introduce them to their God and to strengthen the foundation of their faith, one of this is Islamic Religious Education which is carried out in their formal education. This research includes a descriptive qualitative field study, to find out the learning model of Islamic Religious Education for Children with physical disabilities in Muhammadiyah Extraordinary School Dekso Kulonprogo. Data collection uses observation, interview and documentation techniques, followed by data analysis through data reduction, data presentation, verification and data validity testing. The results showed that the Muhammadiyah Extraordinary School Dekso used a 2013 curriculum that was modified according to the characteristics of their students. To reduce the difficulty level of students, the subject and indicators of learning are simplified, the material is delivered in easy language with concrete media. Learning approach for mentally retarded children is directed at individual and remidiative approaches. Assessment is based on verbal evaluation, practice and daily observations of students.